A cost-utility analysis of BRCA1 and BRCA2 testing in high-risk breast cancer patients and family members in Thailand: a cost-effective policy in resource-limited settings - Lertwilaiwittaya, Pongtawat; Tantai, Narisa; Maneeon, Satanun; Kongbunrak, Sophittha; Nonpanya, Nongyao; Hurst, Anna C. E.; Srinonprasert, Varalak; Pithukpakorn, Manop (Frontiers in Public Health, 2023)
Background: Screening for germline pathogenic BRCA1 or BRCA2 variants (gBRCA) in high-risk breast cancer patients is known to be cost-effective in high-income countries. Nationwide adoption of genetics testing in high-risk breast cancer population remains poor. Our study aimed to assess gBRCA health economics data in the middle-income country setting, Thailand.Methods: Decision tree and Markov model were utilized to assess cost-utility between the testing versus no-testing groups from societal perspective and lifetime horizon. We interviewed 264 patients with breast/ovarian cancer and their family members to assess relevant costs and quality of life using EQ-5D-5L. One-way sensitivity, probabilistic sensitivity (Monte Carlo simulation) and budget impact analyses were done to estimate the outcome under Thailand's Universal Health Coverage scheme.Results: The predicted lifetime cost and Quality-adjusted Life Year (QALY) for those with breast cancer were $13,788 and 10.22 in the testing group and $13,702 and 10.07 in the no-testing group. The incremental cost-effectiveness ratio for gBRCA testing in high-risk breast cancer patients was $573/QALY. The lifetime cost for the family members of those with gBRCA was $14,035 (QALY 9.99), while the no-testing family members group was $14,077 (QALY 9.98). Performing gBRCA testing in family members was cost saving.Cost-utility analysis demonstrated a cost-effectivene result of gBRCA testing in high-risk breast cancer patients and cost-saving in familial cascade testing. The result was endorsed in the national health benefits package in 2022. Other middle-income countries may observe the costeffective/cost-saving aspects in common genetics disease under their national health schemes.